Malocclusion in primary dentition: a cross-sectional study in a Lisbon population - Pimenta,Carolina (2023)
Abstract Objectives: To study the prevalence of malocclusion in deciduous dentition and its associated factors. Methods: The target population consisted of children between 3 and 5 years old who attended four kindergartens in Alvalade, Lisbon. Data was collected through a questionnaire to parents and an intraoral examination of children. The questionnaire collected sociodemographic and non-nutritive sucking habits information. The intraoral examination collected data about the child’s occlusion and dental caries. Results: The sample included 89 children. The prevalence of malocclusion was 83.9%, and the most prevalent types were crowding (44.8%) and distocclusion (41.4%). Most of the children (68.2%) had non-nutritive sucking habits, of which using a pacifier was the most frequente (81.6%). The habit of using a pacifier after three years of age was reported by 67.8% of the participants. The variables statistically associated with malocclusion (p<0.05) were age, mother’s education level, non-nutritive sucking habits, use of pacifiers and thumb sucking, and caries in primary teeth. Conclusions: The prevalence of malocclusion and non-nutritive sucking habits was high. Early diagnosis and intervention are important to avoid serious malocclusion problems and structural and functional changes.